IMPACT OF COMPOST, INORGANIC PHOSPHORUS FERTILIZERS AND THEIR COMBINATION ON MAIZE GROWTH, YIELD, NUTRIENT UPTAKE AND SOIL PROPERTIES - M. Zafar; M. K. Abbasi; T. Arjumend; K. Jabran (Journal of Animal and Plant Sciences, 2012)
Effect of compost (COM) and four inorganic phosphorus (P) sources, diammonium phosphate (DAP), single super phosphate (SSP), nitrophos (NP) and triple super phosphate (TSP) either alone or in combination on growth, yield and nutrient uptake of maize and their effect on soil properties was studied. Each of the inorganic P source and COM either alone or in combination (50:50 ratio) were applied to supply 90 kg P ha-1. The results indicated that conjunctive use of inorganic P sources and COM significantly (P < 0.05) increased plant height, leaf area and chlorophyll content. Grain, dry matter, biomass yield and protein content increased by 10-61, 40-67, 30-67 and 17-46% over control. P uptake increased 17 g kg-1 in control to 29 g kg-1 where DAP and COM was combined. The results also indicated that combine use of inorganic P with COM resulted in significant increase in total N (13−75%), available P (7−57%) and available K (7−20%) compared to control. In addition, increase in plant N accumulation and P uptake associated with combined treatments would help to minimize the use of high cost inorganic P fertilizers for sustainable agro ecosystem.
Keywords: phosphorus sources; yield; protein; compost; maize; soil properties